2018
DOI: 10.1016/j.orcp.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of obesity and metabolic syndrome in Tibetan immigrants living in high altitude areas in Ladakh, India

Abstract: Among this group of Tibetan immigrants living in high altitude areas, women have a higher prevalence of obesity and MetS than men. No relationship was found between diabetes and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
17
1
3
Order By: Relevance
“…In Mongolians aged over 18 years, the prevalence of MetS in men was higher than in women (36•7% vs. 17•8%) [24]. However, a study of Tibetan immigrants in India aged over 20 years reported a prevalence of 10•6% in men and 33•3% in women [27]. In our study, Tibetans had a much lower prevalence of MetS as a result of possible volunteer bias.…”
Section: Discussioncontrasting
confidence: 64%
“…In Mongolians aged over 18 years, the prevalence of MetS in men was higher than in women (36•7% vs. 17•8%) [24]. However, a study of Tibetan immigrants in India aged over 20 years reported a prevalence of 10•6% in men and 33•3% in women [27]. In our study, Tibetans had a much lower prevalence of MetS as a result of possible volunteer bias.…”
Section: Discussioncontrasting
confidence: 64%
“…As a result, it leads to decrease in blood glucose, haemoglobin A1c and increase insulin sensitivity. Moreover, the cold weather and chronic hypoxia at high altitude cause calorie intake increase and energy expenditure decrease, which eventually leads to positive energy gain, and induces overweight and obesity 17. Our study revealed that although living altitude affected the risk of different components of metabolic syndrome, there was no dose–response effect between altitude and the risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 66%
“…We identified MetS in more than half of the study population, which is comparable to the figures from other national, regional and international studies conducted in Egypt, 8,14 Saudi Arabia, 15-17 the United Arab Emirates, 18 Kuwait, 19 Oman, 20 and Turkey. 21 Lower rates were reported in Qatar (28.0%), 22 Italy (33.0% in the general population vs 70% in the obese population), 23,24 Greece (23.6%), 25 China (24.2%), 26 Mexico (41.0%), 27 India (20.0%), 28 the United States (24%-32%), 29,30 and across Europe (24.3%). 31 The growing burden of abdominal obesity and MetS and consequently the accelerated development of DM and CVD are explained by transitions toward unhealthy patterns in regard to socioeconomic characteristics, lifestyle factors, and nutritional status that are ongoing in these communities.…”
Section: Discussionmentioning
confidence: 96%